Difference between revisions of "2019 AIME I Problems/Problem 11"

(Solution 2)
(17 intermediate revisions by 7 users not shown)
Line 1: Line 1:
 
==Problem 11==
 
==Problem 11==
  
In <math>\triangle ABC</math>, the sides have integers lengths and <math>AB=AC</math>. Circle <math>\omega</math> has its center at the incenter of <math>\triangle ABC</math>. An ''excircle'' of <math>\triangle ABC</math> is a circle in the exterior of <math>\triangle ABC</math> that is tangent to one side of the triangle and tangent to the extensions of the other two sides. Suppose that the excircle tangent to <math>\overline{BC}</math> is internally tangent to <math>\omega</math>, and the other two excircles are both externally tangent to <math>\omega</math>. Find the minimum possible value of the perimeter of <math>\triangle ABC</math>.
+
In <math>\triangle ABC</math>, the sides have integer lengths and <math>AB=AC</math>. Circle <math>\omega</math> has its center at the incenter of <math>\triangle ABC</math>. An ''excircle'' of <math>\triangle ABC</math> is a circle in the exterior of <math>\triangle ABC</math> that is tangent to one side of the triangle and tangent to the extensions of the other two sides. Suppose that the excircle tangent to <math>\overline{BC}</math> is internally tangent to <math>\omega</math>, and the other two excircles are both externally tangent to <math>\omega</math>. Find the minimum possible value of the perimeter of <math>\triangle ABC</math>.
  
 
==Solution 1==
 
==Solution 1==
Line 14: Line 14:
 
-franchester
 
-franchester
  
==Solution 2==
+
==Solution 2 (Lots of Pythagorean Theorem)==
 +
 
 
<asy>
 
<asy>
size(8cm);
 
defaultpen(fontsize(80pt));
 
pair A, B, C, I, IA, IB, IC;
 
A=(0, 4sqrt(5));
 
B=(-1, 0);
 
C=(1, 0);
 
I=incenter(A, B, C);
 
IA=2*circumcenter(I,B,C)-I;
 
IB=2*circumcenter(I,C,A)-I;
 
IC=2*circumcenter(I,A,B)-I;
 
  
draw(B -- A -- C); draw(IB -- IC); draw(incircle(A, B, C));
+
unitsize(1cm);
draw(foot(IB, B, C) -- foot(IC, B, C));
+
 
draw(circle(IA, length(IA-foot(IA, B, C))));
+
 
draw(arc(IB, IB-(4sqrt(5), 0), IB-(0, 4sqrt(5))));
+
var x = 9;
draw(arc(IC, IC-(0, 4sqrt(5)), IC+(4sqrt(5), 0)));
+
 
draw(circle(I, 2/sqrt(5)+sqrt(5)));
+
pair A = (0,sqrt(x^2-1));
 +
pair B = (-1,0);
 +
pair C = (1,0);
 +
 
 +
dot(Label("$A$",A,NE),A);
 +
dot(Label("$B$",B,SW),B);
 +
dot(Label("$C$",C,SE),C);
 +
 
 +
draw(A--B--C--cycle);
 +
 
 +
 
 +
var r = sqrt((x-1)/(x+1));
 +
 
 +
pair I = (0,r);
 +
dot(Label("$I$",I,SE),I);
 +
draw(circle(I,r));
 +
draw(Label("$r$"),I--I+r*SSW,dashed);
 +
 
 +
 
 +
pair M = intersectionpoint(A--B,circle(I,r));
 +
pair N = (0,0);
 +
pair O = intersectionpoint(A--C,circle(I,r));
 +
 
 +
dot(Label("$M$",M,W),M);
 +
dot(Label("$N$",N,S),N);
 +
dot(Label("$O$",O,E),O);
 +
 
 +
var rN = sqrt((x+1)/(x-1));
 +
 
 +
pair EN = (0,-rN);
 +
dot(Label("$E_N$",EN,SE),EN);
 +
draw(circle(EN,rN));
 +
draw(Label("$r_N$"),EN--EN+rN*SSW,dashed);
 +
 
 +
 
 +
pair AB = (-1-2/(x-1),-2rN);
 +
pair AC = (1+2/(x-1),-2rN);
 +
 
 +
draw(B--AB,EndArrow);
 +
draw(C--AC,EndArrow);
 +
 
 +
pair H = intersectionpoint(B--AB,circle(EN,rN));
 +
dot(Label("$H$",H,W),H);
 +
 
 +
 
 +
var rM = sqrt(x^2-1);
 +
 
 +
pair EM = (-x,rM);
 +
dot(Label("$E_M$",EM,SW),EM);
 +
draw(Label("$r_M$"),EM--EM+rM*SSE,dashed);
 +
 
 +
 
 +
pair CB = (-x-1,0);
 +
pair CA = (-2/x,sqrt(x^2-1)+2(sqrt(x^2-1)/x));
 +
 
 +
draw(B--CB,EndArrow);
 +
draw(A--CA,EndArrow);
 +
 
 +
 
 +
pair J = intersectionpoint(A--B,circle(EM,rM));
 +
pair K = intersectionpoint(B--CB,circle(EM,rM));
 +
 
 +
dot(Label("$J$",J,W),J);
 +
dot(Label("$K$",K,S),K);
 +
 
 +
 
 +
draw(arc(EM,rM,-100,15),Arrows);
  
dot("$A$", A, N);
 
dot("$B$", B, SW);
 
dot("$C$", C, SE);
 
dot("$I$", I, N);
 
dot("$I_A$", IA, S);
 
dot("$I_B$", IB, NE);
 
dot("$I_C$", IC, NW);
 
 
</asy>
 
</asy>
First assume that <math>BC=2</math> and <math>AB=AC=x</math>, and scale up later. Notice that <math>\overline{I_BAI_C}\parallel\overline{BC}</math> (<math>\textbf{Note:}</math> This is wrong. The two excircles B and C, by definition, must be externally tangent to AB and AC. However, this solution says that the two excircles are tangent at A, which means they are tangent to the same line. However, we know that AB and AC are distinct, a contradiction. Therefore, this solution is wrong.)
 
  
Then, the height from <math>A</math> is <math>\sqrt{x^2-1}</math>, so if <math>K=[ABC]</math>, we know <math>K=\sqrt{x^2-1}</math>. Then, if <math>r_D</math> denotes the <math>D</math>-exradius for <math>D\in\{A,B,C\}</math> and <math>s=x+1</math> denotes the semiperimeter, <cmath>r_A=\frac{K}{s-2}=\frac{K}{x-1},\;r_b=r_C=\frac{K}{s-x}=K,\text{ and }r=\frac{K}{s}=\frac{K}{x+1}.</cmath>Then, if <math>X</math> denotes the tangency point between the <math>B</math>-excircle and <math>\overline{BC}</math>, it is known that <math>BX=s</math>, so <math>AI_B=s-1=x</math>. Furthermore, <math>AI=\sqrt{(s-2)^2+r^2}=\sqrt{(x-1)^2+(K/(x+1))^2}</math>. Then, <cmath>r+2r_A=II_A=II_B-r_B.</cmath>It follows that
+
First, assume <math>BC=2</math> and <math>AB=AC=x</math>. The triangle can be scaled later if necessary. Let <math>I</math> be the incenter and let <math>r</math> be the inradius. Let the points at which the incircle intersects <math>AB</math>, <math>BC</math>, and <math>CA</math> be denoted <math>M</math>, <math>N</math>, and <math>O</math>, respectively.
<cmath>
+
 
\begin{align*}
+
 
II_B&=r+2r_A+r_B\\
+
Next, we calculate <math>r</math> in terms of <math>x</math>. Note the right triangle formed by <math>A</math>, <math>I</math>, and <math>M</math>. The length <math>IM</math> is equal to <math>r</math>. Using the Pythagorean Theorem, the length <math>AN</math> is <math>\sqrt{x^2-1}</math>, so the length <math>AI</math> is <math>\sqrt{x^2-1}-r</math>. Note that <math>BN</math> is half of <math>BC=2</math>, and by symmetry caused by the incircle, <math>BN=BM</math> and <math>BM=1</math>, so <math>MA=x-1</math>. Applying the Pythagorean Theorem to <math>AIM</math>, we get
\sqrt{AI^2+AI_B^2}&=\frac{K}{x+1}+\frac{2K}{x-1}+K\\
+
<cmath>r^2+(x-1)^2=\left(\sqrt{x^2-1}-r\right)^2.</cmath>
\sqrt{x^2+(x-1)^2+\left(\frac{K}{x+1}\right)^2}&=K\left(\frac1{x+1}+\frac2{x-1}+1\right)\\
+
Expanding yields
\frac{\sqrt{(x^2+(x-1)^2)(x+1)^2+x^2-1}}{x+1}&=K\left(\frac{x^2+3x}{x^2-1}\right)\\
+
<cmath>r^2+x^2-2x+1=x^2-1-2r\sqrt{x^2-1}+r^2,</cmath>
\frac{\sqrt{2x^3(x+1)}}{x+1}&=\frac{x(x+3)}{\sqrt{x^2-1}}\\
+
which can be simplified to
2x(x-1)&=x^2+6x^2+9\\
+
<cmath>2r\sqrt{x^2-1}=2x-2.</cmath>
0&=x^2-8x-9\\
+
Dividing by <math>2</math> and then squaring results in
&=(x+1)(x-9),
+
<cmath>r^2(x^2-1)=(x-1)^2,</cmath>
\end{align*}
+
and isolating <math>r^2</math> gets us
</cmath>
+
<cmath>r^2=\frac{(x-1)^2}{x^2-1}=\frac{(x-1)^2}{(x+1)(x-1)}=\frac{x-1}{x+1},</cmath>
whence <math>x=9</math>. Then, since <math>\gcd(2,9,9)=1</math>, the smallest possible perimeter is <math>2+9+9=\boxed{020}</math>.
+
so <math>r=\sqrt{\frac{x-1}{x+1}}</math>.
 +
 
 +
 
 +
We then calculate the radius of the excircle tangent to <math>BC</math>. We denote the center of the excircle <math>E_N</math> and the radius <math>r_N</math>.
 +
 
 +
Consider the quadrilateral formed by <math>M</math>, <math>I</math>, <math>E_N</math>, and the point at which the excircle intersects the extension of <math>AB</math>, which we denote <math>H</math>. By symmetry caused by the excircle, <math>BN=BH</math>, so <math>BH=1</math>.
 +
 
 +
Note that triangles <math>MBI</math> and <math>NBI</math> are congruent, and <math>HBE</math> and <math>NBE</math> are also congruent. Denoting the measure of angles <math>MBI</math> and <math>NBI</math> measure <math>\alpha</math> and the measure of angles <math>HBE</math> and <math>NBE</math> measure <math>\beta</math>, straight angle <math>MBH=2\alpha+2\beta</math>, so <math>\alpha + \beta=90^\circ</math>. This means that angle <math>IBE</math> is a right angle, so it forms a right triangle.
 +
 
 +
Setting the base of the right triangle to <math>IE</math>, the height is <math>BN=1</math> and the base consists of <math>IN=r</math> and <math>EN=r_N</math>. Triangles <math>INB</math> and <math>BNE</math> are similar to <math>IBE</math>, so <math>\frac{IN}{BN}=\frac{BN}{EN}</math>, or <math>\frac{r}{1}=\frac{1}{r_N}</math>. This makes <math>r_N</math> the reciprocal of <math>r</math>, so <math>r_N=\sqrt{\frac{x+1}{x-1}}</math>.
 +
 
 +
 
 +
Circle <math>\omega</math>'s radius can be expressed by the distance from the incenter <math>I</math> to the bottom of the excircle with center <math>E_N</math>. This length is equal to <math>r+2r_N</math>, or <math>\sqrt{\frac{x-1}{x+1}}+2\sqrt{\frac{x+1}{x-1}}</math>. Denote this value <math>r_\omega</math>.
 +
 
 +
 
 +
Finally, we calculate the distance from the incenter <math>I</math> to the closest point on the excircle tangent to <math>AB</math>, which forms another radius of circle <math>\omega</math> and is equal to <math>r_\omega</math>. We denote the center of the excircle <math>E_M</math> and the radius <math>r_M</math>. We also denote the points where the excircle intersects <math>AB</math> and the extension of <math>BC</math> using <math>J</math> and <math>K</math>, respectively. In order to calculate the distance, we must find the distance between <math>I</math> and <math>E_M</math> and subtract off the radius <math>r_M</math>.
 +
 
 +
We first must calculate the radius of the excircle. Because the excircle is tangent to both <math>AB</math> and the extension of <math>AC</math>, its center must lie on the angle bisector formed by the two lines, which is parallel to <math>BC</math>. This means that the distance from <math>E_M</math> to <math>K</math> is equal to the length of <math>AN</math>, so the radius is also <math>\sqrt{x^2-1}</math>.
 +
 
 +
Next, we find the length of <math>IE_M</math>. We can do this by forming the right triangle <math>IAE_M</math>. The length of leg <math>AI</math> is equal to <math>AN</math> minus <math>r</math>, or <math>\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}</math>. In order to calculate the length of leg <math>AE_M</math>, note that right triangles <math>AJE_M</math> and <math>BNA</math> are congruent, as <math>JE_M</math> and <math>NA</math> share a length of <math>\sqrt{x^2-1}</math>, and angles <math>E_MAJ</math> and <math>NAB</math> add up to the right angle <math>NAE_M</math>. This means that <math>AE_M=BA=x</math>.
 +
 
 +
Using Pythagorean Theorem, we get
 +
<cmath>IE_M=\sqrt{\left(\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}\right)^2+x^2}.</cmath>
 +
Bringing back
 +
<cmath>r_\omega=IE_M-r_M</cmath>
 +
and substituting in some values, the equation becomes
 +
<cmath>r_\omega=\sqrt{\left(\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}\right)^2+x^2}-\sqrt{x^2-1}.</cmath>
 +
Rearranging and squaring both sides gets
 +
<cmath>\left(r_\omega+\sqrt{x^2-1}\right)^2=\left(\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}\right)^2+x^2.</cmath>
 +
Distributing both sides yields
 +
<cmath>r_\omega^2+2r_\omega\sqrt{x^2-1}+x^2-1=x^2-1-2\sqrt{x^2-1}\sqrt{\frac{x-1}{x+1}}+\frac{x-1}{x+1}+x^2.</cmath>
 +
Canceling terms results in
 +
<cmath>r_\omega^2+2r_\omega\sqrt{x^2-1}=-2\sqrt{x^2-1}\sqrt{\frac{x-1}{x+1}}+\frac{x-1}{x+1}+x^2.</cmath>
 +
Since
 +
<cmath>-2\sqrt{x^2-1}\sqrt{\frac{x-1}{x+1}}=-2\sqrt{(x+1)(x-1)\frac{x-1}{x+1}}=-2(x-1),</cmath>
 +
We can further simplify to
 +
<cmath>r_\omega^2+2r_\omega\sqrt{x^2-1}=-2(x-1)+\frac{x-1}{x+1}+x^2.</cmath>
 +
Substituting out <math>r_\omega</math> gets
 +
<cmath>\left(\sqrt{\frac{x-1}{x+1}}+2\sqrt{\frac{x+1}{x-1}}\right)^2+2\left(\sqrt{\frac{x-1}{x+1}}+2\sqrt{\frac{x+1}{x-1}}\right)\sqrt{x^2-1}=-2(x-1)+\frac{x-1}{x+1}+x^2</cmath>
 +
which when distributed yields
 +
<cmath>\frac{x-1}{x+1}+4+4\left(\frac{x+1}{x-1}\right)+2(x-1+2(x+1))=-2(x-1)+\frac{x-1}{x+1}+x^2.</cmath>
 +
After some canceling, distributing, and rearranging, we obtain
 +
<cmath>4\left(\frac{x+1}{x-1}\right)=x^2-8x-4.</cmath>
 +
Multiplying both sides by <math>x-1</math> results in
 +
<cmath>4x+4=x^3-x^2-8x^2+8x-4x+4,</cmath>
 +
which can be rearranged into
 +
<cmath>x^3-9x^2=0</cmath>
 +
and factored into
 +
<cmath>x^2(x-9)=0.</cmath>
 +
This means that <math>x</math> equals <math>0</math> or <math>9</math>, and since a side length of <math>0</math> cannot exist, <math>x=9</math>.
 +
 
 +
 
 +
As a result, the triangle must have sides in the ratio of <math>9:2:9</math>. Since the triangle must have integer side lengths, and these values share no common factors greater than <math>1</math>, the triangle with the smallest possible perimeter under these restrictions has a perimeter of <math>9+2+9=\boxed{020}</math>. ~[[User:emerald_block|emerald_block]]
 +
 
 +
==Solution 3 (Not that hard construction)==
 +
Notice that the <math>A</math>-excircle would have to be very small to fit the property that it is internally tangent to <math>\omega</math>, given that circle <math>\omega</math>'s centre is at the incenter of <math>\triangle ABC</math>. If <math>BC=2</math>, we see that <math>AB=AC</math> must be somewhere in the <math>6</math> to <math>13</math> range. If we test <math>6</math> by construction, we notice the <math>A</math>-excircle is too big for it to be internally tangent to <math>\omega</math>. This means we should test <math>8</math> or <math>9</math> next. I actually did this and found that <math>9</math> worked, so the answer is <math>2+9+9=\boxed{20}</math>. Note that <math>BC</math> cannot be <math>1</math> because then <math>AB=AC</math> would have to be <math>4.5</math> which is not an integer.
 +
 
 +
~[[User:Icematrix2|icematrix2]]
  
(Solution by TheUltimate123)
+
==Video Solution (On the Spot STEM)==
  
==Solution 3==
+
https://www.youtube.com/watch?v=zKHwTJBhKdM
  
On the Spot STEM solves this problem here: https://www.youtube.com/watch?v=zKHwTJBhKdM
+
==Video Solution 2 (I would recommend this one because it's more concise)==
  
Please like, share, and subscribe!
+
https://www.youtube.com/watch?v=ldr4yi3t6hQ
  
 
==See Also==
 
==See Also==
 
{{AIME box|year=2019|n=I|num-b=10|num-a=12}}
 
{{AIME box|year=2019|n=I|num-b=10|num-a=12}}
 
{{MAA Notice}}
 
{{MAA Notice}}

Revision as of 17:05, 19 September 2020

Problem 11

In $\triangle ABC$, the sides have integer lengths and $AB=AC$. Circle $\omega$ has its center at the incenter of $\triangle ABC$. An excircle of $\triangle ABC$ is a circle in the exterior of $\triangle ABC$ that is tangent to one side of the triangle and tangent to the extensions of the other two sides. Suppose that the excircle tangent to $\overline{BC}$ is internally tangent to $\omega$, and the other two excircles are both externally tangent to $\omega$. Find the minimum possible value of the perimeter of $\triangle ABC$.

Solution 1

Let the tangent circle be $\omega$. Some notation first: let $BC=a$, $AB=b$, $s$ be the semiperimeter, $\theta=\angle ABC$, and $r$ be the inradius. Intuition tells us that the radius of $\omega$ is $r+\frac{2rs}{s-a}$ (using the exradius formula). However, the sum of the radius of $\omega$ and $\frac{rs}{s-b}$ is equivalent to the distance between the incenter and the the $B/C$ excenter. Denote the B excenter as $I_B$ and the incenter as $I$. Lemma: $I_BI=\frac{2b*IB}{a}$ We draw the circumcircle of $\triangle ABC$. Let the angle bisector of $\angle ABC$ hit the circumcircle at a second point $M$. By the incenter-excenter lemma, $AM=CM=IM$. Let this distance be $\alpha$. Ptolemy's theorem on $ABCM$ gives us \[a\alpha+b\alpha=b(\alpha+IB)\to \alpha=\frac{b*IB}{a}\] Again, by the incenter-excenter lemma, $II_B=2IM$ so $II_b=\frac{2b*IB}{a}$ as desired. Using this gives us the following equation: \[\frac{2b*IB}{a}=r+\frac{2rs}{s-a}+\frac{rs}{s-b}\] Motivated by the $s-a$ and $s-b$, we make the following substitution: $x=s-a, y=s-b$ This changes things quite a bit. Here's what we can get from it: \[a=2y, b=x+y, s=x+2y\] It is known (easily proved with Heron's and a=rs) that \[r=\sqrt{\frac{(s-a)(s-b)(s-b)}{s}}=\sqrt{\frac{xy^2}{x+2y}}\] Using this, we can also find $IB$: let the midpoint of $BC$ be $N$. Using Pythagorean's Theorem on $\triangle INB$, \[IB^2=r^2+(\frac{a}{2})^2=\frac{xy^2}{x+2y}+y^2=\frac{2xy^2+2y^3}{x+2y}=\frac{2y^2(x+y)}{x+2y}\] We now look at the RHS of the main equation: \[r+\frac{2rs}{s-a}+\frac{rs}{s-b}=r(1+\frac{2(x+2y)}{x}+\frac{x+2y}{y})=r(\frac{x^2+5xy+4y^2}{xy})=\frac{r(x+4y)(x+y)}{xy}=\frac{2(x+y)IB}{2y}\] Cancelling some terms, we have \[\frac{r(x+4y)}{x}=IB\] Squaring, \[\frac{2y^2(x+y)}{x+2y}=\frac{(x+4y)^2*xy^2}{x^2(x+2y)}\to \frac{(x+4y)^2}{x}=2(x+y)\] Expanding and moving terms around gives \[(x-8y)(x+2y)=0\to x=8y\] Reverse substituting, \[s-a=8s-8b\to b=\frac{9}{2}a\] Clearly the smallest solution is $a=2$ and $b=9$, so our answer is $2+9+9=\boxed{020}$ -franchester

Solution 2 (Lots of Pythagorean Theorem)

[asy]  unitsize(1cm);   var x = 9;  pair A = (0,sqrt(x^2-1)); pair B = (-1,0); pair C = (1,0);  dot(Label("$A$",A,NE),A); dot(Label("$B$",B,SW),B); dot(Label("$C$",C,SE),C);  draw(A--B--C--cycle);   var r = sqrt((x-1)/(x+1));  pair I = (0,r); dot(Label("$I$",I,SE),I); draw(circle(I,r)); draw(Label("$r$"),I--I+r*SSW,dashed);   pair M = intersectionpoint(A--B,circle(I,r)); pair N = (0,0); pair O = intersectionpoint(A--C,circle(I,r));  dot(Label("$M$",M,W),M); dot(Label("$N$",N,S),N); dot(Label("$O$",O,E),O);  var rN = sqrt((x+1)/(x-1));  pair EN = (0,-rN); dot(Label("$E_N$",EN,SE),EN); draw(circle(EN,rN)); draw(Label("$r_N$"),EN--EN+rN*SSW,dashed);   pair AB = (-1-2/(x-1),-2rN); pair AC = (1+2/(x-1),-2rN);  draw(B--AB,EndArrow); draw(C--AC,EndArrow);  pair H = intersectionpoint(B--AB,circle(EN,rN)); dot(Label("$H$",H,W),H);   var rM = sqrt(x^2-1);  pair EM = (-x,rM); dot(Label("$E_M$",EM,SW),EM); draw(Label("$r_M$"),EM--EM+rM*SSE,dashed);   pair CB = (-x-1,0); pair CA = (-2/x,sqrt(x^2-1)+2(sqrt(x^2-1)/x));  draw(B--CB,EndArrow); draw(A--CA,EndArrow);   pair J = intersectionpoint(A--B,circle(EM,rM)); pair K = intersectionpoint(B--CB,circle(EM,rM));  dot(Label("$J$",J,W),J); dot(Label("$K$",K,S),K);   draw(arc(EM,rM,-100,15),Arrows);  [/asy]

First, assume $BC=2$ and $AB=AC=x$. The triangle can be scaled later if necessary. Let $I$ be the incenter and let $r$ be the inradius. Let the points at which the incircle intersects $AB$, $BC$, and $CA$ be denoted $M$, $N$, and $O$, respectively.


Next, we calculate $r$ in terms of $x$. Note the right triangle formed by $A$, $I$, and $M$. The length $IM$ is equal to $r$. Using the Pythagorean Theorem, the length $AN$ is $\sqrt{x^2-1}$, so the length $AI$ is $\sqrt{x^2-1}-r$. Note that $BN$ is half of $BC=2$, and by symmetry caused by the incircle, $BN=BM$ and $BM=1$, so $MA=x-1$. Applying the Pythagorean Theorem to $AIM$, we get \[r^2+(x-1)^2=\left(\sqrt{x^2-1}-r\right)^2.\] Expanding yields \[r^2+x^2-2x+1=x^2-1-2r\sqrt{x^2-1}+r^2,\] which can be simplified to \[2r\sqrt{x^2-1}=2x-2.\] Dividing by $2$ and then squaring results in \[r^2(x^2-1)=(x-1)^2,\] and isolating $r^2$ gets us \[r^2=\frac{(x-1)^2}{x^2-1}=\frac{(x-1)^2}{(x+1)(x-1)}=\frac{x-1}{x+1},\] so $r=\sqrt{\frac{x-1}{x+1}}$.


We then calculate the radius of the excircle tangent to $BC$. We denote the center of the excircle $E_N$ and the radius $r_N$.

Consider the quadrilateral formed by $M$, $I$, $E_N$, and the point at which the excircle intersects the extension of $AB$, which we denote $H$. By symmetry caused by the excircle, $BN=BH$, so $BH=1$.

Note that triangles $MBI$ and $NBI$ are congruent, and $HBE$ and $NBE$ are also congruent. Denoting the measure of angles $MBI$ and $NBI$ measure $\alpha$ and the measure of angles $HBE$ and $NBE$ measure $\beta$, straight angle $MBH=2\alpha+2\beta$, so $\alpha + \beta=90^\circ$. This means that angle $IBE$ is a right angle, so it forms a right triangle.

Setting the base of the right triangle to $IE$, the height is $BN=1$ and the base consists of $IN=r$ and $EN=r_N$. Triangles $INB$ and $BNE$ are similar to $IBE$, so $\frac{IN}{BN}=\frac{BN}{EN}$, or $\frac{r}{1}=\frac{1}{r_N}$. This makes $r_N$ the reciprocal of $r$, so $r_N=\sqrt{\frac{x+1}{x-1}}$.


Circle $\omega$'s radius can be expressed by the distance from the incenter $I$ to the bottom of the excircle with center $E_N$. This length is equal to $r+2r_N$, or $\sqrt{\frac{x-1}{x+1}}+2\sqrt{\frac{x+1}{x-1}}$. Denote this value $r_\omega$.


Finally, we calculate the distance from the incenter $I$ to the closest point on the excircle tangent to $AB$, which forms another radius of circle $\omega$ and is equal to $r_\omega$. We denote the center of the excircle $E_M$ and the radius $r_M$. We also denote the points where the excircle intersects $AB$ and the extension of $BC$ using $J$ and $K$, respectively. In order to calculate the distance, we must find the distance between $I$ and $E_M$ and subtract off the radius $r_M$.

We first must calculate the radius of the excircle. Because the excircle is tangent to both $AB$ and the extension of $AC$, its center must lie on the angle bisector formed by the two lines, which is parallel to $BC$. This means that the distance from $E_M$ to $K$ is equal to the length of $AN$, so the radius is also $\sqrt{x^2-1}$.

Next, we find the length of $IE_M$. We can do this by forming the right triangle $IAE_M$. The length of leg $AI$ is equal to $AN$ minus $r$, or $\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}$. In order to calculate the length of leg $AE_M$, note that right triangles $AJE_M$ and $BNA$ are congruent, as $JE_M$ and $NA$ share a length of $\sqrt{x^2-1}$, and angles $E_MAJ$ and $NAB$ add up to the right angle $NAE_M$. This means that $AE_M=BA=x$.

Using Pythagorean Theorem, we get \[IE_M=\sqrt{\left(\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}\right)^2+x^2}.\] Bringing back \[r_\omega=IE_M-r_M\] and substituting in some values, the equation becomes \[r_\omega=\sqrt{\left(\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}\right)^2+x^2}-\sqrt{x^2-1}.\] Rearranging and squaring both sides gets \[\left(r_\omega+\sqrt{x^2-1}\right)^2=\left(\sqrt{x^2-1}-\sqrt{\frac{x-1}{x+1}}\right)^2+x^2.\] Distributing both sides yields \[r_\omega^2+2r_\omega\sqrt{x^2-1}+x^2-1=x^2-1-2\sqrt{x^2-1}\sqrt{\frac{x-1}{x+1}}+\frac{x-1}{x+1}+x^2.\] Canceling terms results in \[r_\omega^2+2r_\omega\sqrt{x^2-1}=-2\sqrt{x^2-1}\sqrt{\frac{x-1}{x+1}}+\frac{x-1}{x+1}+x^2.\] Since \[-2\sqrt{x^2-1}\sqrt{\frac{x-1}{x+1}}=-2\sqrt{(x+1)(x-1)\frac{x-1}{x+1}}=-2(x-1),\] We can further simplify to \[r_\omega^2+2r_\omega\sqrt{x^2-1}=-2(x-1)+\frac{x-1}{x+1}+x^2.\] Substituting out $r_\omega$ gets \[\left(\sqrt{\frac{x-1}{x+1}}+2\sqrt{\frac{x+1}{x-1}}\right)^2+2\left(\sqrt{\frac{x-1}{x+1}}+2\sqrt{\frac{x+1}{x-1}}\right)\sqrt{x^2-1}=-2(x-1)+\frac{x-1}{x+1}+x^2\] which when distributed yields \[\frac{x-1}{x+1}+4+4\left(\frac{x+1}{x-1}\right)+2(x-1+2(x+1))=-2(x-1)+\frac{x-1}{x+1}+x^2.\] After some canceling, distributing, and rearranging, we obtain \[4\left(\frac{x+1}{x-1}\right)=x^2-8x-4.\] Multiplying both sides by $x-1$ results in \[4x+4=x^3-x^2-8x^2+8x-4x+4,\] which can be rearranged into \[x^3-9x^2=0\] and factored into \[x^2(x-9)=0.\] This means that $x$ equals $0$ or $9$, and since a side length of $0$ cannot exist, $x=9$.


As a result, the triangle must have sides in the ratio of $9:2:9$. Since the triangle must have integer side lengths, and these values share no common factors greater than $1$, the triangle with the smallest possible perimeter under these restrictions has a perimeter of $9+2+9=\boxed{020}$. ~emerald_block

Solution 3 (Not that hard construction)

Notice that the $A$-excircle would have to be very small to fit the property that it is internally tangent to $\omega$, given that circle $\omega$'s centre is at the incenter of $\triangle ABC$. If $BC=2$, we see that $AB=AC$ must be somewhere in the $6$ to $13$ range. If we test $6$ by construction, we notice the $A$-excircle is too big for it to be internally tangent to $\omega$. This means we should test $8$ or $9$ next. I actually did this and found that $9$ worked, so the answer is $2+9+9=\boxed{20}$. Note that $BC$ cannot be $1$ because then $AB=AC$ would have to be $4.5$ which is not an integer.

~icematrix2

Video Solution (On the Spot STEM)

https://www.youtube.com/watch?v=zKHwTJBhKdM

Video Solution 2 (I would recommend this one because it's more concise)

https://www.youtube.com/watch?v=ldr4yi3t6hQ

See Also

2019 AIME I (ProblemsAnswer KeyResources)
Preceded by
Problem 10
Followed by
Problem 12
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15
All AIME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS